Outcome of two-week head and neck cancer pathway for the otolaryngology department in a tertiary centre. Issue 10 (5th October 2021) - Mettias, B; Charlton, A; Ashokkumar, S
Abstract: Background: The two-week-wait head and neck cancer referral pathway was introduced by the Department of Health, and refined through National Institute for Health and Care Excellence guidelines which were updated in 2015. Methods: A retrospective study was conducted of two-week-wait referrals to out-patient ENT from January to June 2018. The analysis included demographics, referral symptoms according to National Institute for Health and Care Excellence 2015 guidelines, cancer pick-up rates and positive predictive values. Results: A total of 1107 patients were referred for suspected head and neck cancer over six months, with 6 per cent diagnosed with cancer. Neck lump, persistent hoarseness and throat pain were the most common presenting symptoms. Neck lump had the highest positive predictive value, followed by oral swelling. Oral bleeding and persistent unilateral sore throat showed significant positive predictive values. Investigation for metastatic head and neck cancer of an unknown primary or the involvement of other multidisciplinary teams could hinder the achievement of a 62-day treatment target. Conclusion: The cancer pick-up rate from two-week-wait referrals is only 1.5 times higher than routine referrals. The 'red flag' symptoms given in the 2015 National Institute for Health and Care Excellence update would benefit from further review.